Delamination of graphite in a high pressure homogenizer1. Issue 71 (2nd August 2015) - Nacken, T. J.; Damm, C.; Walter, J.; Rüger, A.; Peukert, W.
<x xml:space="preserve">Abstract</x> A scalable industrial method for graphene and Few-Layer-Graphene (FLG) production by graphite delamination in N-methylpyrrolidone and water–surfactant mixtures using a high pressure homogenizer is presented.